EVALUASI PRAKTIK AKUNTABILITAS PEMERINTAHAN DI KOTA KENDARI - Andi Syaiful Zainal; Riston G Ahmad; Murniati; Andi Awaluddin Ma’ruf; La Ode Abdul Harlan (Journal Publicuho, 2024)
This study evaluates government accountability practices in Kendari City as a representation of the condition of local government in Indonesia. Qualitative methods were used by involving various parties, and the results showed the Kendari City government's focus on efficiency, effectiveness, transparency, and community participation. The evaluation results are based on the use of Key Performance Indicators and Government Institutional Accountability and Performance Reports. The Kendari City Government maintains the Unqualified Fair opinion of BPK RI, even though there are indicators that have not been achieved. Policy recommendations include proactive publication, bureaucratic reform, increased transparency through financial reports, and community empowerment. This research is expected to provide guidance for stakeholders in improving accountability and quality of local governance in Kendari City.